The Optimization Ratio and Size of Raw Materials in Patchouli Oil Extraction Process Using Hydrodistillation Method with Addition of MgCl2 - Afifah, Dian Ayu; Cendekia, Devy; Teguh, Dedi (Universitas Islam Indonesia, 2024)
This research focuses on optimizing patchouli oil yield using the hydrodistillation method and adding MgCl2 as the main component. The RSM method is used to analyze model variance, including the sum of squares model, less of the fit model, and ANOVA analysis. The research results show that adding MgCl2 can increase the yield of patchouli oil by reducing water content and undesirable non-volatile elements, thereby producing more stable patchouli oil. ANOVA analysis of patchouli oil yield was carried out to determine the optimal results from factors such as F/S, material size, and time. The extraction time factor had a p-value of less than 0.05, indicating that the model was suitable for explaining the results. The research results showed that the yield of patchouli oil was optimal with an F/S ratio of 0.075, material size of 20 mesh, and extraction time of 5 hours, with a yield of 0.1 gr/mL being the best choice. The research results showed that the use of specific methods, namely distilled water and MgCl2 in the extraction process, was effective in increasing the yield of patchouli oil